PENGOLAHAN LIMBAH CAIR INDUSTRI PUPUK UREA MENGGUNAKAN FILTER KERAMIK - Subriyer Nasir (Purifikasi, 2011)
The purpose of this research was to design the liquid waste treatment system using ceramic membrane filtration method. The ceramic filter was made of a mixture of clay and coal fly-ash with certain compositions. Rig in this experiment was equipped with PVC piping system, flowmeter, pressure gauge, and the circulation pump. The liquid waste tested was obtained from the secondary effluent of a fertilizer industry. The measured were feed flow rate, permeate flow rate, Total Dissolved Solid (TDS), pH, heavy metal content, and ammonia contents according to the Indonesian National Standards (SNI) of effluent water quality. The results showed that ceramic membrane could decrease the ammonia concentration in the secondary effluent up to 96%. Heavy metal ions (Fe, Cr and Mn) could be reduced to 60.9%, 39.4% and 38.4% respectively. The best composition of membrane/filter was achieved at a ratio of 77.5% clay, 20% fly ash and 2.5% of iron powder.